Keseimbangan Foremilk dan Hindmilk Asi pada Ibu Menyusui - Suci Rahmani Nurita (Jurnal Akademika Baiturrahim Jambi, 2021)
The infant morbidity rate is the second indicator in determining the child's health status because it is a reflection of the baby's weak immune system. This is influenced by nutritional factors, socio-economic factors and demographics. Breastfeeding is related to the fulfillment of infant nutrition. Almost all babies in Indonesia (96%) have received breast milk but the infant mortality and morbidity rate is still high. It was found that the duration of breastfeeding greatly affects the survival of the baby, which is related to the imbalance of nutrients the baby gets while breastfeeding. The imbalance between the foremilk and hindmilk can cause problems for the baby such as discomfort and pain. Babies can become fussy, the consistency of the stool becomes watery, green and foamy, spit up, bloating and even diarrhea in babies. This research is descriptive in nature. The objective of this research is to describe the balance of foremilk and hindmilk of breast milk in breastfeeding mothers. The population in this study were all mothers who exclusively breastfed who had babies aged 1-12 months in the working area of the Kenali Besar Community Health Center. Sampling using accidental sampling technique with a sample size of 35 people. Data collection was carried out in January-February 2020 at the Kenali Besar CommunityHealth Center of Jambi City by interview using a questionnaire. The research results were analyzed by univariate. The results showed more than half of the respondents had poor knowledge (65.7%), positive attitudes (51.4%), abnormal length of breastfeeding (68.6%), and proper breastfeeding position and attachment (80%). .As many as 65.7% of respondents have an imbalanced of foremilk and hindmilk of breast milk. It is hoped that the health center and health workers will improve health promotion programs through counseling and exposure to lactation management regarding the balance of foremilk and hindmilk breast milk. It is hoped that breastfeeding mothers can balance the foremilk and hindmilk of breast milk by paying attention to the length of breastfeeding as well as the position and attachment during breastfeeding